2016
DOI: 10.1155/2016/1073192
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Its Associated Factors among Pregnant Women Attending Antenatal Care in Health Institutions of Arba Minch Town, Gamo Gofa Zone, Ethiopia: A Cross-Sectional Study

Abstract: Background. Anemia during pregnancy is a major cause of morbidity and mortality of pregnant women in developing countries and has both maternal and fetal consequences. Despite its known serious effect on health, there is very little research based evidence on this vital public health problem in Gamo Gofa zone in general and in Arba Minch town of Southern Ethiopia in particular. Therefore, this study aims to assess the prevalence and factors associated with anemia among pregnant women attending antenatal care i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
88
14
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(151 citation statements)
references
References 14 publications
43
88
14
6
Order By: Relevance
“…This could be due to the fact that the requirement for iron increases during pregnancy for the growing fetus and placenta, the blood volume of pregnant woman decreases by 50% during this period as a result, supplementation of iron during pregnancy is critical to fulfil this requirement. 26 The finding of this study is in agreement with other previous studies conducted in Ethiopia, Uganda, Nigeria, Vietnam and Pakistan which pointed out that lack of iron supplementation is amongst the most significant risk factors for developing anaemia in pregnant women. [27][28][29][30][31] Thus, this give the impression that the most effective intervention to reduce the prevalence of anemia among pregnant women is education in the proper use of iron and folic acid supplements as well as proper nutrition which contain iron-rich food sources.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could be due to the fact that the requirement for iron increases during pregnancy for the growing fetus and placenta, the blood volume of pregnant woman decreases by 50% during this period as a result, supplementation of iron during pregnancy is critical to fulfil this requirement. 26 The finding of this study is in agreement with other previous studies conducted in Ethiopia, Uganda, Nigeria, Vietnam and Pakistan which pointed out that lack of iron supplementation is amongst the most significant risk factors for developing anaemia in pregnant women. [27][28][29][30][31] Thus, this give the impression that the most effective intervention to reduce the prevalence of anemia among pregnant women is education in the proper use of iron and folic acid supplements as well as proper nutrition which contain iron-rich food sources.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with other studies conducted in India, Ethiopia, Nigeria and Saudi Arabia, which found that pregnant women with less interval than 2 years spacing between previous and index pregnancy were more likely to get anaemia. 26,29,[37][38][39] Therefore, intervention focusing on birth intervals could be appropriate in order to reduce the prevalence of anaemia among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Bekele et al, conducted a cross-sectional study to assess the prevalence and factors associated with anemia among pregnant women attending antenatal care in health institutions of Arba Minch town, Gamo Gofa zone, Southern Ethiopia, who mentioned that birth spacing was independent predictors of anemia in pregnancy, which was consistent to the results of present study [23].…”
Section: Resultssupporting
confidence: 86%
“…This study shows negative association with birth interval, thatiswomen who delay giving birth were 71% less likely to be anemic during pregnancy. Theresult of this is congruent to study conducted inIndia (Kolar District) whichstates that as the birth interval increase, the probability of being anemic is decreased among pregnant women and Study conducted in Arba Minch(Ethiopia) shows that having birth interval less than two years is significantly associated anemia in a pregnant women [27,28]. The similarity may be due to the fact that as birth interval is less than two years high bleeding during birthmay lead anemia.…”
Section: Discussionsupporting
confidence: 84%